Phytochemical and in Vivo Biological Studies of Tanaecium Bilabiatum (Sprague) L.G. Lohmann - Hasan, Mursalin Al; Kuddus, Md Ruhul; Rashid , Mohammad A; Haque , Mohammad Rashedul (Bangladesh Journal of Botany, 2023)
Phytochemical analysis of Tanaecium bilabiatum leaf led to the isolation and identification of salacinin C, daturadiol and a mixture of triterpenes, α-amyrin and β-amyrin. Besides chemical analysis, the methanol extract of T. bilabiatum leaf, METBL was evaluated for analgesic, anti-diarrheal and hypoglycemic potential in mice model. For analgesic activity test by tail immersion technique, the extract significantly extended the percent elongation time of thermal nociception. METBL (400 mg/kg bw) also established the highest inhibition of formalin-induced abdominal writhing (69.39%) in mice, which was comparable with the standard aspirin (75.51%). Likewise, dose-dependent antidiarrheal activity was observed in this test. After oral administration, METBL demonstrated maximum inhibition (40.93%) of castor oil-induced diarrhea in mice. In oral glucose tolerance test, the plant extract produced significant (p < 0.05) hypoglycemic activity. Therefore, it is concluded that T. bilabiatum is a promising source of bioactive compounds with analgesic, antidiarrheal and hypoglycemic potential. Bangladesh J. Bot. 52(1): 119-127, 2023 (March)